1998
DOI: 10.1159/000026323
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Sympathetic Denervation Alters Both the Primary and Memory Cellular Immune Responses to Herpes simplex Virus Infection

Abstract: Numerous studies have sought to delineate the impact of neuroendocrine function on overall immune responsiveness. Using various murine models, we and others have previously shown that both adrenal-dependent and adrenal-independent mechanisms associated with psychological stress modulate components of both the primary and memory cellular immune responses to herpes simplex virus type 1 (HSV-1) infection. We have extended these studies by determining the impact of 6-hydroxydopamine (6-OHDA)-mediated peripheral sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 34 publications
(55 reference statements)
0
12
1
Order By: Relevance
“…In contrast to our findings, Bonneau and colleagues (25) reported that 6-OHDA decreases T CD8ϩ responses to i.p. infections with herpes simplex virus (HSV).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our findings, Bonneau and colleagues (25) reported that 6-OHDA decreases T CD8ϩ responses to i.p. infections with herpes simplex virus (HSV).…”
Section: Discussioncontrasting
confidence: 99%
“…infections with herpes simplex virus (HSV). This discrepancy could be explained by numerous differences between the studies, particularly the timing of 6-OHDA treatment, because Bonneau ablated the SNS 24 h after viral infection (25). Because 6-OHDA treatment can greatly modify innate immune responses (13,16), this could contribute to the differences between our findings and those of Bonneau and colleagues (25).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The importance of innervated immune organs is underscored by findings that suggest disruption of noradrenergic fibers using the neurotoxin, 6-hydroxydopamine (6OHDA) results in changes in antibody production (Livnat et al, 1985;Kohm and Sanders, 1999), delayed-type hypersensitivity responses (Madden et al, 1989), natural killer (NK) cell activity (Reder et al, 1989), and T cell proliferation (Moynihan et al, 2004) which collectively, can modify host susceptibility to infection (Leo et al, 1998;Miura et al, 2001) and severity of autoimmune disease including experimental autoimmune encephalitis (Chelmicka-Schorr et al, 1988) and experimental rheumatoid arthritis (Felton et al, 1992;Härle et al, 2005). 6OHDA treatment results in the activation of the hypothalamic pituitary adrenal axis leading to an elevation in circulating corticosterone (Leo et al, 1998), a potent immunomodulator (McEwen et al, 1997). Likewise, 6OHDA treatment in adult rodents results in the reversible destruction of noradrenergic termini through a loss in membrane integrity elicited by the production of hydrogen peroxide and hydroxyl radicals (Picklo, 1997).…”
Section: Introductionmentioning
confidence: 99%